Rethinking legal reasoning - Samuel, Geoffrey, 1947- (Rethinking law, 2018)
Rethinking legal reasoning seems a bold aim given the large amount of literature devoted to this topic. In this thought-provoking book, Geoffrey Samuel proposes a different way of approaching legal reasoning by examining the topic through the context of legal knowledge (epistemology). What is it to have knowledge of legal reasoning? At a more specific level the pursuit of this understanding is conducted through posing a number of questions that are founded on different approaches. What has legal reasoning been? What are the institutional and conceptual legacies of this history? What is the literature and textual heritage? How does it compare with medical reasoning and with reasoning in the humanities? Can it be demystified? In exploring these questions Samuel suggests a number of frameworks that offer some new insights into the nature of legal reasoning. The author also puts forward two key ideas. First, that the legal notion of an 'interest' might perhaps be a very suitable artefact for rethinking legal reasoning; and, secondly, that fiction theory might be the most viable 'epistemological attitude' for understanding, if not rethinking, reasoning in law. This book will be of great interest to academics who are researching legal method and legal reasoning, as well as epistemology of the social sciences and aspects of comparative law. It will also be an insightful text for those interested in legal history and historical perspectives on legal reasoning.